2023
DOI: 10.3390/cryst13081250
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Microstructural Defects on High-Cycle Fatigue of Ti Grade 2 Manufactured by PBF-LB and Hydrostatic Extrusion

Abstract: The aim of this study was to show the effect of manufacturing defects in a commercially pure Ti Grade 2 produced by a laser beam powder bed fusion (PBF-LB) process on its high-cycle fatigue life. For this purpose, the high-cycle fatigue performance of PBF-LB Ti Grade 2 was compared to its ultrafine-grained (UFG) counterpart processed by hydrostatic extrusion exhibiting a similar mechanical properties under static tensile. The yield strength of the PBF-LB and UFG Ti Grade 2 was 740 and 783 MPa, respectively. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 58 publications
0
0
0
Order By: Relevance
“…The PBF-LB process for HCF samples fabricated in Set III.1 was kept in 0.1-0.3 vol.% of oxygen in the building chamber, so the resulting part had 0.13 wt.% of oxygen measured in the high-temperature extraction method. Furthermore, a study on manufacturing defects in PBF-LB fabricated titanium grade 1, as reported by Majchrowicz et al [49], indicated that a significantly lower endurance fatigue limit was observed while the yield strength was similar to the commercial material. Therefore, the fabrication method should be improved to eliminate the presence of porosity.…”
Section: Discussionmentioning
confidence: 79%
“…The PBF-LB process for HCF samples fabricated in Set III.1 was kept in 0.1-0.3 vol.% of oxygen in the building chamber, so the resulting part had 0.13 wt.% of oxygen measured in the high-temperature extraction method. Furthermore, a study on manufacturing defects in PBF-LB fabricated titanium grade 1, as reported by Majchrowicz et al [49], indicated that a significantly lower endurance fatigue limit was observed while the yield strength was similar to the commercial material. Therefore, the fabrication method should be improved to eliminate the presence of porosity.…”
Section: Discussionmentioning
confidence: 79%